Immunization Completion in Infants Born at Low Birth Weight. (23rd September 2017) - Nestander, Matt; Dintaman, Jay; Susi, Apryl; Gorman, Gregory; Hisle-Gorman, Elizabeth
Abstract : Low birth weight significantly affects immunization completion, even after controlling for prematurity, neonatal illness, provider consistency, access to care, well-child care, and outpatient visits. Complete well-child care visits are associated with immunization completion. Abstract: Background: Low birth weight (LBW) has been associated with underimmunization. We sought to understand the effect of LBW on immunization completion after controlling for previously hypothesized mediators, including prematurity, neonatal illness, well-child care, non–well-child visits, and provider consistency. Methods: We formed a retrospective cohort of infants born between 2008 and 2011 with ≥2 years of military healthcare follow-up. International Classification of Diseases, Ninth Revision codes were used to identify LBW, preterm birth, neonatal illnesses, well-child visits, non–well-child visits, provider consistency, and parental rank in the inpatient and outpatient records. Immunization records were extracted from both records. Logistic regression determined the odds of immunization completion and well-child care completion (ie, having had ≥6 WCC visits by 15 months of age). Results: Of 135964 included infants, 116521 (85.7%) were completely immunized at the age of 2 years. In adjusted analysis, the odds of immunization completion were significantly decreased in infants born at LBW (odds ratio [OR], 0.88 [95% confidence interval (CI), 0.79–0.97]), very LBW (OR, 0.61 [95% CI, 0.48–0.77]), or extremely LBW (OR, 0.45 [95% CI, 0.33–0.63]) or at ≤32 weeks' gestation (OR, 0.76 [95% CI, 0.63–0.92]), infants with chronic lung disease (OR, 0.63 [95% CI, 0.45–0.88]), male infants (OR, 0.96 [95% CI, 0.93–0.99]), and infants who experienced decreased provider consistency (OR, 0.92 [95% CI, 0.91–0.92]). The rate of immunization completion increased with the overall number of healthcare visits (OR, 1.02 [95% CI, 1.02–1.02]) and complete well-child care (OR, 1.80 [95% CI, 1.75–1.86]). However, children born LBW or preterm were significantly less likely to have complete well-child care. Conclusions: After adjustment for preterm birth, comorbid neonatal conditions, and early childhood patterns of healthcare use, LBW was significantly associated with immunization noncompletion in a universal healthcare system. Provider consistency and well-child care seem important for increasing immunization completion in LBW infants.